2013
DOI: 10.1186/2251-712x-9-18
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of shock absorber process parameters using failure mode and effect analysis and genetic algorithm

Abstract: The various process parameters affecting the quality characteristics of the shock absorber during the process were identified using the Ishikawa diagram and by failure mode and effect analysis. The identified process parameters are welding process parameters (squeeze, heat control, wheel speed, and air pressure), damper sealing process parameters (load, hydraulic pressure, air pressure, and fixture height), washing process parameters (total alkalinity, temperature, pH value of rinsing water, and timing), and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…solutions. This algorithm represents more general approximate solution procedure applicable to a large variety of optimization problems (e.g., in Izadi and Kimiagari 2014;AriaNezhad et al 2013;and Mariajayaprakash et al 2013), since it is tailored to solve various optimization problems in diverse research fields. It has been shown that metaheuristics are able to tackle instances of problems that are believed to be hard in general, by exploring usually large solution search spaces of the instances.…”
Section: Solution Methodologymentioning
confidence: 99%
“…solutions. This algorithm represents more general approximate solution procedure applicable to a large variety of optimization problems (e.g., in Izadi and Kimiagari 2014;AriaNezhad et al 2013;and Mariajayaprakash et al 2013), since it is tailored to solve various optimization problems in diverse research fields. It has been shown that metaheuristics are able to tackle instances of problems that are believed to be hard in general, by exploring usually large solution search spaces of the instances.…”
Section: Solution Methodologymentioning
confidence: 99%
“…The results showed that the cooling time was the most effective factor for LPDE followed by refilling pressure and injection pressure was found to be the least effective factor. Mariajayaprakash et al (2013) found the optimum process parameters of shock absorber process using failure mode and effect analysis and genetic algorithm. Chen et al (2013) studied on simultaneous optimization of multiple interrelated quality indices, leading to product quality improvement in the field of plastic injection molding.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Risks with higher RPN values are assumed to be more important and are given higher priorities over others (Mariajayaprakash et al 2013). Each potential risk associated with the MPD process is scored in relation to O, S and D (refer Table 7).…”
Section: Failure Mode and Effect Analysis (Fmea)mentioning
confidence: 99%